Integrated Thematic Teaching Materials with PjBL Based on Book Creator Application in Grade IV Elementary School - Diren Agasi; Desyandri (Jurnal Ilmiah Sekolah Dasar, 2022)
Integrated thematic learning has the aim of presenting complete learning and experience for students. However, the data and information obtained at the research stage through interviews involving teachers and IV grade students Elementary School still obtained the use of printed teaching materials which were not attractive because the paper material used was paper newspaper type. So that the use of teaching materials cannot attract the attention of students, according to several studies, it causes students' understanding and knowledge to be not optimal. This study aims to create and determine the validity of integrated thematic teaching materials with the PjBL model based on the book creator application in the IV grade of elementary school. This development research uses the Borg and Gall model. Where the research starts from the stages of potential and problems to product trials. The instruments used in this research activity are interviews and validation sheets. Based on the problems found at the potential and problem stages, teaching materials were designed with the PjBL model based on the book creator application. Where after being validated by five validators, the following results were found, the language aspect in the valid category, the content aspect in the very valid category, the presentation aspect in the valid category, and the graphic aspect in the very valid category.